Acute perforating appendicitis caused by metastatic squamous cell carcinoma from the lung: A case report. (2020) - Shiraishi, Toshio; Araki, Masato; Sumida, Yorihisa; Fujita, Tomohiro; Hashimoto, Shintaro; Nishimuta, Masato; Matsumoto, Takamune; Hamada, Kiyoaki; Baba, Masayuki; Murakami, Goushi; Wakata, Kouki; Inamura, Yukio; et al.
Highlights: Extremely rare case of appendiceal metastasis of squamous cell carcinoma of the lung. Metastatic appendiceal tumor tend to perforate. Surgery is recommended. CT and PET-CT are useful for diagnosis. Abstract: Introduction: Lung cancer is one of the most common cancers. On the other hand, lung cancer metastasis to the appendix is extremely rare, and in many cases it has been diagnosed with the onset of acute perforating appendicitis. Presentation of case: An 85-year-old man with fever and abdominal pain visited our hospital. He had a history of squamous cell carcinoma of the left upper and lower lobes, metastasis to the ipsilateral lung and femur. CT showed that a finding of acute perforating appendicitis, emergency cecal resection was performed. Examination of the resected specimen showed that the appendix was thickened overall, with a white nodular structure at the root and a perforation in the middle. The final diagnosis was acute perforating appendicitis caused by metastatic squamous cell carcinoma from the lung. The patient had no particular problems during the postoperative course. Discussion: A PubMed search was performed, this appears to be the first reported case of appendiceal metastasis of squamous cell carcinoma of the lung. Since squamous cell carcinoma of the lung has a stronger tendency for local extension than other histological types, perforating appendicitis due to distant metastasis to the abdominal organs and metastasis to the appendix was reported as a very valuable case. Conclusion: Because the progression of concomitant or secondary appendicitis is rapid, we recommend frequent imaging modalities, prophylactic appendectomy be considered for patients who also have lung cancer and imaging findings show suspected metastasis to the appendix.